Implementation Strategies to Increase Clinical Trial Enrollment in a Community-Academic Partnership and Impact on Hispanic Representation: An Interrupted Time Series Analysis. Issue 5 (11th May 2022) - Ledesma Vicioso, Nahomy; Lin, Diana; Gomez, Daniel R.; Yang, Jonathan T.; Lee, Nancy Y.; Rimner, Andreas; Yamada, Yoshiya; Zelefsky, Michael J.; Kalman, Noah S.; Rutter, Charles E.; Kotecha, Rupesh R.; Mehta, Minesh P.; et al.
Abstract : PURPOSE: Community-academic partnerships have the potential to improve access to clinical trials for under-represented minority patients who more often receive cancer treatment in community settings. In 2017, the Memorial Sloan Kettering (MSK) Cancer Center began opening investigator-initiated clinical trials in radiation oncology in targeted community-based partner sites with a high potential to improve diverse population accrual. This study evaluates the effectiveness of a set of implementation strategies for increasing overall community-based enrollment and the resulting proportional enrollment of Hispanic patients on trials on the basis of availability in community-based partner sites. METHODS: An interrupted time series analysis evaluating implementation strategies was conducted from April 2018 to September 2021. Descriptive analysis ofHispanic enrollment on investigator-initiated randomized therapeutic radiation trials open at community-based sites was compared with those open only at themain academic center. RESULTS: Overall, 84 patients were enrolled in clinical trials in the MSK Alliance, of which 48 (56%) identified as Hispanic. The quarterly patient enrollment pre- vs postimplementation increased from 1.39 (95% CI, –3.67 to 6.46) to 9.42 (95% CI, 2.05 to 16.78; P5 .017). In the investigator-initiated randomized therapeutic radiation trials open in the MSK Alliance, Hispanic representation was 11.5% and 35.9% in twometastatic trials and 14.2% in a proton versus photon trial. Inmatched trials open only at the main academic center, Hispanic representation was 5.6%, 6.0%, and 4.0%, respectively. CONCLUSION: A combination of practice-level and physician-level strategies implemented at community-based partner sites was associated with increased clinical trial enrollment, which translated to improved Hispanic representation. This supports the role Q:2 of strategic community-academic partnerships in addressing disparities in clinical trial enrollment. Abstract : Strategies to Increase Clinical Trial Enrollment in Community-Academic Partnership and Hispanic Representation.